The Thun-Hohenstein album : cultures of remembrance in a paper armory - Kirchhoff, Chassica (Armour and weapons., 2023)
The first extensive study of the depiction of the armour in the Thun-Hohenstein Album, in the vibrant artistic and cultural contexts that created it.